Increased productivity, competitiveness and sustainability of systems of small and medium livestock producers in the Patía Basin and Popayán Plateau - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Under agreement with CIAT and led by the Universidad del Cauca, new forage technologies are being introduced and evaluated using a participatory approach working with small- and medium-sized livestock producers from northern Cauca, Colombia. The project aims to identify, assess and co-develop germplasm of forage species suitable for the conditions of Patía and Popayan, and also to evaluate the production and use of high-quality forages incorporated into farming systems.